2021
DOI: 10.3390/su13148053
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning in Survival Mode: Students and Faculty Perceptions of Distance Education during the COVID-19 Lockdown

Abstract: (1) This study demonstrates how a Saudi university has responded to the COVID-19 lockdown in order to examine the success factors and highlight any challenges. The main purpose was to determine the perceptions of students and faculty towards emergency online distance learning from a teaching and learning perspective; (2) A cross-faculty study was conducted: two different self-administered questionnaires were developed for students and faculty, respectively. In addition, data was collected from official reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…Our study findings show that ‘Not going to the university’ and ‘Not having a routine life’ significantly contribute to the signs and symptoms of stress experienced by students during e-learning. These findings contradict two previous studies from Saudi Arabia, which collected data during the early times of pandemic from a well-reputed higher educational institute in Saudi Arabia [ 3 , 25 ]. These studies reported that a larger proportion of students had positive perceptions about e-learning and were satisfied with their study experiences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study findings show that ‘Not going to the university’ and ‘Not having a routine life’ significantly contribute to the signs and symptoms of stress experienced by students during e-learning. These findings contradict two previous studies from Saudi Arabia, which collected data during the early times of pandemic from a well-reputed higher educational institute in Saudi Arabia [ 3 , 25 ]. These studies reported that a larger proportion of students had positive perceptions about e-learning and were satisfied with their study experiences.…”
Section: Discussioncontrasting
confidence: 99%
“…“Online Distance Education” or ‘E-learning” refers to an institution based formal education where both students and instructors are isolated, and it utilizes interactive telecommunications systems to connect teachers, learners and other learning resources [ 2 ]. E-learning during the COVID-19 pandemic was the most sustainable way to continue studies as per the academic calendar [ 3 ]. Thus, a majority of the countries around the globe directed educational institutions to implement online studies at all levels, which prevented the spread of the COVID-19 and facilitated the continuation of the studies during the last academic year [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…So teachers are willing to use both new and existing resources and methodologies to achieve their teaching goals and engage students through online teaching [ 31 , 32 ]. In addition, faculty members are actively engaged in updating their knowledge on distance education [ 33 ], keeping mental activeness among students [ 34 ], and writing research papers. Rapid (and often improvised) adjustments to work methodology, with uncertain measured results and often based on intuition, have caused stress and nervousness in teachers.…”
Section: Introductionmentioning
confidence: 99%
“…A study has confirmed that there are three factors relevant for examination: student satisfaction, instructor satisfaction and institutional satisfaction [79]. Satisfaction with an online education system is important for all three parties because it strengthens motivation and engagement in all areas of education [80]. In this paper, we focus on a more complex analysis of instructor satisfaction and the effects of the COVID-19 pandemic on online teaching.…”
Section: Discussionmentioning
confidence: 99%